Thresholds of asset size and ownership structure impact on profit rate: Case study of Vietnamese commercial banks listed on the HOSE - Nguyen, Kim Phuoc; Tran , Thi Tuong Van (Journal of Finance - Marketing Research, 2025)
Recent studies on the performance of businesses in general and commercial banks in particular have shown that size is an important factor affecting the performance or profitability of businesses. The size of commercial banks in Vietnam has certain differences. Studies supporting the theory of economies of scale argue that the larger the size, the higher the efficiency (Hughes & Mester, 2013; Shehzad, De Haan & Scholtens, 2013). Some other studies have found a negative relationship between size and profit, profitability of banks (Feng & Serlestis, 2010; De Haan & Poghosyan, 2012a, b). Hansen (1999) proposed a threshold regression model (Threshold estimate model) to help determine the threshold value that changes the impact of size on performance. Based on Hansen’s model (1999), banks with an asset size exceeding 𝑒11.2261≈75,064.24 (Prob = 0.4770) no asset threshold exists. The regression results show that 6/7 independent variables have an impact on ROA of the banks in the research sample. This is the scientific basis for bank managers to study and adjust the ownership structure and decide to increase their assets in the future in a reasonable way, bringing the highest profitability.